Perceptions towards COVID-19 and adoption of preventive measures among the public in Saudi Arabia: a cross sectional study - Ghadah Alkhaldi; Ghadeer S. Aljuraiban; Sultana Alhurishi; Roberta De Souza; Kethakie Lamahewa; Rosa Lau; Fahdah Alshaikh (BMC, 2021)
Abstract Background Effective management of the spread of a novel infectious disease, such as the COVID-19 virus can be achieved through influencing people's behavior to adopt preventive measures. The public's perceptions and attitudes towards the virus, governmental guidance and preventive measures were unknown in Saudi Arabia. Objectives 1) investigate the public perception of COVID-19, anxiety level, the COVID-19 information sources sought, adoption of preventive measures, and ability and willingness to self-isolate during and post-lockdown periods of the COVID-19 pandemic in Saudi Arabia; 2) investigate socio-demographic factors associated with adoption of preventive measures against COVID-19 and self-isolation practices. Method Between April 22nd and June 21st 2020, Saudi adults aged ≥18 years voluntarily completed a self-administered web-based cross-sectional survey, distributed through social media (WhatsApp) and emails to representatives in education, health, business, and social sectors across all Saudi Arabian regions. The survey included questions on anxiety level, COVID-19 risk perceptions and adoption of preventive measures. Weighted percentages, Pearson's chi-square tests, and multiple logistic regression were applied to evaluate associations between these factors and socio-demographic variables. Results A total of 2393 respondents completed the survey. A majority (74%) were worried about the COVID-19 outbreak and of those, 27% reported that it was likely that they would be infected with COVID-19; 16% believed it would be life-threatening or severe. However, only 11% of respondents reported high anxiety level. Adoption of hygiene practices and social distancing were lower among older (> 65 years) compared to younger (18-24 years) respondents (OR: 0.06; 95% CI: 0.01, 0.28 and OR 0.06; 95% CI: 0.01, 0.27 respectively). High percentages of respondents reported being able to (88%) and were willing to (82%) self-isolate. Those with the lowest gross household income and those with at least one flu symptom were less able and willing to self-isolate. A significant increase in levels of anxiety, perceived effectiveness of social distancing and hygiene practices was reported in the post-lockdown compared to during the lockdown. Conclusions The study reported high levels of adoption of preventive measures, willingness and perceived ability to self-isolate during the early phase of the pandemic. Vulnerable groups such as the elderly, and those with low socio-economic status reported lower adoption of preventive measures or ability and willingness to self-isolate. Tailored public health messages and interventions are needed to achieve high adherence to these preventive measures in these groups.